(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
It was originally believed that only mass could create Black Holes. It is the purpose of this paper to prove that the charge from White Dwarf Stars creates the majority of Black Holes. Stars with mass below 1.44 Solar mass known as the Chandrasekhar Limit create White Dwarf Stars. Using the energy in charge, Energy = /(24 where n corresponds to the number of electrons, White Dwarfs are responsible for Solar Mass type or smaller Black Holes with charge. Stars bigger than 1.44 Solar Mass create bigger size Black Holes without charge such as those from Neutron Stars or those located at the center of a galaxy using the energy of mass, Energy = m . Since there are more stars smaller in size than the sun, a majority of charged Black Holes are created by White Dwarf Stars. We calculate the size of the Schwarzschild Radius of the White Dwarf as R = /(12 ) where n corresponds to the number of electrons drawn from the White Dwarf and sent into the Black Hole created. Only White Dwarf Stars can create Black Holes with Mass, Angular Momentum, and Charge, albeit these Black Holes will be smaller in size than those created by mass.